Eleição é tapeação: luta armada é a solução: leituras, experiências e construção do consensus bellicu na nova esquerda marxista Cearense (1962-1976) - Costa, Henri Randel (2009)
This dissertation deals with the political action of some historical subjects than in the late sixties and early seventies of last century, concluded that armed struggle would be the most rational and feasible to address civil-military dictatorship imposed on the country 1964, even if taking other possibilities of opposition to the capitalists and their authoritarian system. In this sense, the understanding of this extreme option, members were privileged and two niches, the readings written committed before and during the armed conflict, as well as the multiple experiences of the rebels, from childhood until the ultimate episodes of strife. Completing this picture, the work also highlights the emergence of a New Left Marxist, a world both locally and nationally, and internationally, marked by the optics of the Cold War.